2014
DOI: 10.1007/s00737-014-0446-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimistic outlook regarding maternity protects against depressive symptoms postpartum

Abstract: Purpose The transition to motherhood is a time of elevated risk for clinical depression. Dispositional optimism may be protective against depressive symptoms; however the arrival of a newborn presents numerous challenges that may be at odds with initially positive expectations, and which may contribute to depressed mood. We have explored the relative contributions of antenatal and postnatal optimism regarding maternity to depressive symptoms in the postnatal period. Methods 98 pregnant women underwent clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 52 publications
4
23
0
1
Order By: Relevance
“…The other approach supports the idea that people's expectations for the future arise from their interpretations of the past and how they give meaning to the things that happened to them [76] Over the past 30 years, the body of research related to dispositional optimism has become increasingly rich, in particular that showing correlations between dispositional optimism and subjective well-being [19] , for instance self-esteem, positive emotions, and life satisfaction [15,[24][25] . On the other hand, negative correlations have been found between dispositional optimism and negative emotions, anxiety, and depression [10,16,[26][27] . Optimism is a very stable trait.…”
Section: Optimism As a Buffer To Emotional Distressmentioning
confidence: 99%
See 2 more Smart Citations
“…The other approach supports the idea that people's expectations for the future arise from their interpretations of the past and how they give meaning to the things that happened to them [76] Over the past 30 years, the body of research related to dispositional optimism has become increasingly rich, in particular that showing correlations between dispositional optimism and subjective well-being [19] , for instance self-esteem, positive emotions, and life satisfaction [15,[24][25] . On the other hand, negative correlations have been found between dispositional optimism and negative emotions, anxiety, and depression [10,16,[26][27] . Optimism is a very stable trait.…”
Section: Optimism As a Buffer To Emotional Distressmentioning
confidence: 99%
“…The review showed statistically significant effec-ts on survival of all-cause mortality in general population, cardiovascular outcomes, immune function, and cancer and pregnancy outcomes. Optimism has also been associated with lower depression symptoms at initial assessment during pregnancy and postpartum, to which optimism therefore appears to yield resistance [16,[33][34] .…”
Section: Optimism As a Buffer To Emotional Distressmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, although a history of psychiatric symptoms predisposes individuals to future psychopathology, positive mental health both supports recovery from distress and protects against poor mental health in the future [ 22 - 25 ]. Studies with pregnant women have found that prenatal positive mental health traits such as positive affect and optimism are protective of postpartum depression [ 26 , 27 ] and birth outcomes such as preterm delivery [ 28 ]. A dual approach aligns with two-factor models of mental health, which recognize distress and well-being as 2 distinct but interrelated continua [ 22 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peripartum depression is a debilitating mood disorder that occurs in 8–15% of childbearing women (Byatt et al, 2016; Robakis et al, 2015). Although several psychosocial risk factors have been identified, a substantial proportion of the risk for the disorder remains unexplained and biological contributors are unclear (Babb et al, 2015).…”
Section: Introductionmentioning
confidence: 99%